Spin-reorientation-induced magnetodielectric coupling effects in two layered perovskite magnets - Huang, Bo; Zhang, Jian-Yu; Huang, Rui-Kang; Chen, Ming-Kun; Xue, Wei; Zhang, Wei-Xiong; Zeng, Ming-Hua; Chen, Xiao-Ming (Chemical science (Cambridge), 2018)
Spin-reorientation-induced magnetodielectric coupling effects were discovered in two layered perovskite magnets, [C 6 H 5 CH 2 CH 2 NH 3 ] 2 [MCl 4 ] (M = Mn 2+ and Cu 2+ ), via isothermal magnetodielectric measurements on single-crystal samples. Specifically, peak-like dielectric anomalies and spin-flop transitions appeared simultaneously at around ±34 kOe for the canted antiferromagnet (M = Mn 2+ ) at below 44.3 K, while a low-field (1 kOe) controlled magnetodielectric effect was observed in the “soft” ferromagnet (M = Cu 2+ ) at below 9.5 K. These isothermal magnetodielectric effects are highly reproducible and synchronous with the field-induced magnetization at different temperatures, well confirming the essential role of spin reorientation on inducing magnetodielectric coupling effects. These findings strongly imply that the layered perovskite magnets are new promising organic–inorganic hybrid systems to host magnetodielectric coupling effects.